Dry anaerobic digestion of cow manure and agricultural products in a full-scale plant: Efficiency and comparison with wet fermentation. (January 2018) - Chiumenti, Alessandro; da Borso, Francesco; Limina, Sonia
Highlights: The first full-scale, agricultural dry fermentation plant of Italy was monitored. Recirculation rate, leachate, biogas and energy production were monitored. Dry fermentation showed biogas yields similar to wet. Retention time, recirculation of digestate and leachate are key factors. Plant operation required significant man labor (loading and unloading of reactors). Abstract: For years, anaerobic digestion processes have been implemented for the management of organic wastes, agricultural residues, and animal manure. Wet anaerobic digestion still represents the most common technology, while dry fermentation, dedicated to the treatment of solid inputs (TS > 20%) can be considered as an emerging technology, not in terms of technological maturity, but of diffusion. The first agricultural dry anaerobic digestion plant constructed in Italy was monitored from the start-up, for over a year. The plant was fed with manure and agricultural products, such as corn silage, triticale, ryegrass, alfalfa, and straw. Three Combined Heat and Power units, for a total installed power of 910 kWe, converted biogas into thermal and electric energy. The monitoring included the determination of quality and quantity of input feedstocks, of digestate (including recirculation rate), of leachate, biogas quality (CH4, CO2, H2 S), biogas yield, energy production, labor requirement for loading, and unloading operations. The results of the monitoring were compared to performance data obtained in several full scale wet digestion plants. The dry fermentation plant revealed a start-up phase that lasted several months, during which the average power resulted in 641 kWe (70.4% of nominal power), and the last period the power resulted in 788 kWe (86.6% of installed power). Improving the balance of the input, the dry fermentation process demonstrated biogas yields similar to wet anaerobic digestion, congruent to the energy potential of the biomasses used in the process. Furthermore, the operation of the plant required significant man labor, mainly related to loading and unloading of the anaerobic cells.